Dual Hydrogen- and Oxygen-Transport Membrane Reactor for Solar-Driven Syngas Production - Tou, Maria; Grylka, Adrian; Schuller, Arnaud; Bulfin, Brendan; Steinfeld, Aldo; Michalsky, Ronald (Frontiers in Energy Research, 2020)
A novel thermochemical dual-membrane reactor is considered with the goal of efficiently converting CO2 to fuels using concentrated solar energy as the process heat source. In contrast to the temperature-swing redox cycle, in this isothermal system the thermolysis of H2O at above 1800 K is assisted by removal of O2 across an oxygen-permeable membrane and of H2 across a hydrogen-permeable membrane. The latter is consumed by a stream of CO2 via the reverse water-gas shift reaction to re-form H2O and continuously generate CO. The net reaction is the splitting of CO2 to CO and ½O2. Because reactions at such high temperature are expected to be thermodynamically controlled, thermodynamic models are developed to calculate the equilibrium limits of the proposed dual-membrane configuration. For comparison, two reference configurations comprising either a single oxygen-permeable membrane or a single hydrogen-permeable membrane are analyzed. At 1800 K, 1 bar total pressure, and (not applicable for the hydrogen-membrane reactor) 10 Pa O2, the equilibrium mole fraction of fuel is 2% with a single oxygen membrane, 4% with a single hydrogen membrane, and 15% in the dual-membrane system. In all cases, total selectivity of CO2 to CO and O2 is obtained. Assuming thermodynamic equilibrium, the solar-to-fuel energy efficiency realistically attainable is 4% with a single oxygen membrane, 8% with a single hydrogen membrane, and 17% in the dual-membrane configuration at the aforementioned conditions. By increasing the pressure of the feed of steam to 100 bar, the dual-membrane model system could theoretically approach full mass conversion of CO2 and reach up to 26% solar-to-fuel energy efficiency. However, developing appropriate and stable ceramic materials for such a system poses a significant challenge.